Highly NIR-emitting ytterbium complexes containing 2-(tosylaminobenzylidene)-N-benzoylhydrazone anions: structure in solution and use for bioimaging. Issue 11 (11th March 2021) - Kovalenko, Anton D.; Pavlov, Alexander A.; Ustinovich, Ilya D.; Kalyakina, Alena S.; Goloveshkin, Alexander S.; Marciniak, Łukasz; Lepnev, Leonid S.; Burlov, Anatolii S.; Schepers, Ute; Bräse, Stefan; Utochnikova, Valentina V.
Abstract : Brightly NIR emissive ytterbium Schiff base complex was predicted by NMR spectroscopy and used for NIR bioimaging. Its structure in solution was determined by NMR spectroscopy. Abstract : Solution behaviour in DMSO using 1D and 2D NMR spectroscopy was performed for lanthanide complexes Ln(L)(HL) and Ln(HL)2 Cl, containing non-macrocyclic 2-(tosylamino)-benzylidene- N -benzoylhydrazone (H2 L), and the structure of [Yb(L)] + cation in solution was determined. Based on the NMR data, the possibility to obtain novel complexes containing [Ln(L)2 ] − was predicted, which was successfully synthesized, and the crystal structure of K(C2 H5 OH)3 [Yb(L)2 ] was determined. Thanks to its high quantum yield of NIR luminescence (1.3 ± 0.2%), high absorption, low toxicity, and the stability of its anion against dissociation in DMSO, K(H2 O)3 [Yb(L)2 ] was successfully used for bioimaging.